Exploring the impact of ward climate and the development of a tool to measure staff culture in forensic community homes - Isgar, Rachel (2022)
Background: Secure settings have a distinct environment. They are intended to manage risk whilst balancing a therapeutic approach. This thesis provides an investigation into organisational factors that impact on staff and patient outcomes in secure and community settings; specifically ward climate and staff culture. Ward climate is a multifactorial construct comprised of the material, social and emotional conditions of a ward and the interaction between these. Culture can be summarised as jointly held views, beliefs, and behaviour across a workplace. Staff culture is multidimensional, ranging from broad organisational levels to within-team facets. Research studies evidence the influence of organisational factors on patient rehabilitation and staff burnout. Aims: Healthcare staff in forensic settings experience some of the highest levels of violence compared to other healthcare professionals. Research has evidenced patient violence has significant impact on rehabilitation, other patients, and staff. The first aim of the thesis was to explore published literature of ward climate, focusing on the impact on patient aggression and staff burnout in secure hospitals. There is a paucity of research on organisational factors that can impact rehabilitation in forensic community homes. To enable future research to explore the impact of organisational factors, the thesis aimed to develop a tool that can measure staff culture in community settings. Method: A review of key concepts, definitions and models was first carried out to provide an overview of the thesis and the background for the research (chapter one). It followed by a systematic review that explored the impact ward climate has on two important issues in secure hospitals; patient aggression and staff burnout. Chapter three provides an overview of the methods considered within the development of the tool to measure staff culture. Chapter four explores staff experiences of working in or supporting forensic community homes. Thematic analysis was used to identify themes and sub-themes relating to culture from interviews undertaken with members of a multidisciplinary team. Findings were used to inform the development of the Cultural Assessment of Staff Teams (CAST), a psychometric tool measuring staff culture. Chapter five describes further development and validation of the CAST tool. It outlines the processes to ascertain face and content validity of items. Item reduction and re-wording were completed following the scoring of the expert feedback. Following cognitive interviews with a sample of the target population (support workers) final amendments were made to the tool. Results: The thesis contributes to the research regarding organisational factors in forensic settings. The systematic review found mixed results. There was an overall finding that the higher the security of the ward the greater the impact ward climate had on patient aggression. Staff burnout and sickness were associated with ward climate. Regarding the tool development, the domains identified to measure staff culture in community settings were ’The Organisation‘, ’Home Manager‘, ’Care Team‘, and ’Risk Management‘. The first version of the tool had 129 items. Once the face and content validity were scored and cognitive interviews were facilitated, the numbers of items decreased to 86. Discussion: This thesis emphasises the importance of forensic settings measuring and responding to organisational factors. The thesis provides an insight into the concepts of staff culture in forensic community homes and has informed the development of the CAST. Compared to inpatient settings there is a lack of published work on the impact of organisational factors in forensic community settings. The CAST will enable further research to be undertaken to identify relationships between staff culture and resident outcomes